Effects of Academic Mobility on Researcher’s Productivity: The Case of African Scholars in Chinese Universities - Zineb Draissi; Yu Rong (Al-Qanṭara, 2024)
We hypothesize that academic mobility enhances scientists' human and social capital, positively influencing academic performance through metrics, publications, research projects, and co-authorship. Using partial least squares structural modeling on a sample of 204 African academics in Chinese institutions, we find that mobility components, particularly the length of stay in China and moving between host institutions, significantly impact cognitive and tacit knowledge. For mobility to boost productivity (publications, projects, and metrics), academics must develop networks with editors, reviewers, and key authors while extending their human capital. Thus, social and human capital are crucial intervening variables in demonstrating academic mobility’s role in enhancing early academics’ productivity.